Science Process Skills Through The Read, Answer, Discuss, Explain And Create (Radec) Learning Model On Science Materials In High School - Sirry Alvina; Syarifah Rita Zahara; Ayu Rahmi; Maulida Aufa Rofiki Lubis; Rahmah Nursada (LPPM Universitas Malikussaleh, 2024)
Natural Sciences (IPA) is a science related to nature that is systematically arranged through an investigation. The RADEC model as one of the solutions in the learning process that accommodates students to exchange information obtained and solve a problem. The purpose of this study is to implement the role of RADEC syntax in triggering student expertise in science process abilities (KPS). Increasing KPS requires the application of the RADEC Model to see the significance of increasing the use of the model, the measuring instrument used to measure KPS is a data collection instrument in the form of an observation sheet that has been prepared and then validated constructively (material experts). Sampling was carried out using convenience sampling, class sampling was carried out using a non-random technique which was then tested statistically as a basis for determining classes with the same abilities. The type of research conducted in this study is Pre-Experimental Design research. The posttest score of students' science process skills in the experimental class had the highest score of 96 and the lowest score of 78. While the posttest score in the control class had the highest score of 89 and the lowest score of 72. The average score of students' science process skills in the experimental class was 86 with a high category and in the control class was 80 with a very moderate category. The average score of students' science process skills in the experimental class was 81.66% with a moderate category. Students' science process skills in the Experimental class obtained the highest percentage on the observing indicator of 93.18% and the lowest percentage on the making a hypothesis indicator of 75.00%. Students' science process skills in the Control class obtained the highest percentage on the observing indicator of 86.36% and the lowest percentage on the making a hypothesis indicator of 61.36%.